Immune Fingerprint in Diabetes: Ocular Surface and Retinal Inflammation - Amorim, Madania Gafur (2023)
Diabetes is a prevalent global health issue associated with significant morbidity and mortality. Diabetic retinopathy (DR) is a well-known inflammatory, neurovascular complication of diabetes and a leading cause of preventable blindness in developed countries among working-age adults. However, the ocular surface components of diabetic eyes are also at risk of damage due to uncontrolled diabetes, which is often overlooked. Inflammatory changes in the corneas of diabetic patients indicate that inflammation plays a significant role in diabetic complications, much like in DR. The eye's immune privilege restricts immune and inflammatory responses, and the cornea and retina have a complex network of innate immune cells that maintain immune homeostasis. Nevertheless, low-grade inflammation in diabetes contributes to immune dysregulation. This article aims to provide an overview and discussion of how diabetes affects the ocular immune system's main components, immune-competent cells, and inflammatory mediators. By understanding these effects, potential interventions and treatments may be developed to improve the ocular health of diabetic patients.